The Potential of Candida Biofilm Protein as Bioreceptor for Candidiasis Immunoassay - Masfufatun Masfufatun; Loo Haryanto; Harsono Harsono (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: Candidiasis or infection that is caused by Candida has become a new list of the therapeutical problems recently. The difficulties in diagnosing are the main cause of the unsatisfactory results from common therapies and diagnosis methods. This has urged researchers to find alternative ways in candidiasis diagnosis such as serology-based detection using antigen or antibody development. The aim of this study was to evaluate the potential of protein derived from Candida albicans biofilm as bioreceptor on candidiasis immunoassay through Dot Blot method. The research method used descriptive method with the following stages: (1) preparation of Candida albicans biofilm (2) extraction of Candida albicans protein through enzymatic and mechanical methods, (3) determination of protein molecular weight with SDS-PAGE (4) production of polyclonal anti- candida and (5) analysis of protein extract as bioreeceptor on dot blot. Profile of biofilm proteins on SDS-PAGE analysis were shown on molecular weight 27,42; 29,89; 38,10; 44,90; 48,75; 52,92; 55,14; 59,86; 70,56; 87,36; 102,54;115,05; 130,14;143,14;181,53 kD. There were differences in the intensity of dots in the control group (44070) and treatment groups (63170.5). It is noticeable that biofilm protein extract of C. albicans can be used for induction of anti-Candida polyclonal antibody production as the potential candidate of bioreceptor in candidiasis immunoassay. Keywords: SDS-PAGE, polyclonal antibody, immunoassay, dot blot, biofilm